THE IMPACT OF COVID-19, MARKET CAPITALIZATION, STOCK TRADING VOLUME, AND LARGE-SCALE SOCIAL RESTRICTIONS ON STOCK RETURNS - Tanjaya, Tasya Novia; Suhendah, Rousilita (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this research is to determine the effect of Covid-19, market capitalization, stock trading volume and large-scale social restrictions on stock returns. This research uses agriculture companies and property, real estate and building construction companies listed in Indonesian Stock Exchange from March 2, 2020 to December 31, 2020. The Covid-19 measured by growth of positive confirmed cases. The results of research in the agriculture sector show that growth of positive confirmed cases has a negative significant influence on stock return, market capitalization has no significant influence on stock return, stock trading volume and large-scale social restrictions have a positive significant influence on stock return. The results of research in the property, real estate and building construction sector show that growth of positive confirmed cases has no significant influence on stock return, market capitalization has a negative significant influence on stock return, stock trading volume and large-scale social restrictions have a positive significant influence on stock return.